Energetic analysis of fatigue hysteresis by thermographic and digital image correlation methodologies. Issue 11 (2nd July 2020) - La Rosa, Guido; Lo Savio, Fabio; Giudice, Fabio; Clienti, Carmelo; Marino Cugno Garrano, Adriana
Abstract: A hysteresis cycle can define the variation in mechanical characteristics of fatigue life and failure response. Traditional analysis is performed using force‐displacement signals derived from the testing equipment, but this approach is prone to large errors due to clearances and slips in the measuring chain. For this reason, the authors here propose a novel setup able to assess accurately the strain status of specimens by digital image correlation (DIC) and a procedure to calculate the hysteresis energy by thermographic analysis in order to measure the damping energy with precision. The results obtained by an experimental investigation on a common austenitic steel (AISI 304) highlight that the hysteresis areas defined by the DIC displacements, and those found by the testing machine outputs have substantial differences in value. The thermal variations and the areas of the hysteresis loops, both linked to the plastic energy, were also compared, showing a reliable correlation.